Sebuah Penelitian Empiris tentang Hubungan Masa Kerja, Kualitas Sumber Daya Manusia dan Komitmen Organisasi - Rahayu Mardikaningsih (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
The relationship between employees and organizations has long been a topic of further research. Working period is a form of the relationship between the two. The results of these relationships can be in the form of organizational commitment and human resource quality. The proposition assumes that the practice and development of human resources is oriented towards the balance of the two parties. To prove the proposition an empirical study was conducted involving three relevant variables, namely tenure, human resource quality and organizational commitment. This study aims to (1) find out the relationship between tenure and human resource quality; (2) to find out the relationship between tenure and organizational commitment; and (3) to determine the relationship between human resource quality and organizational commitment. The analysis tool uses correlation analysis through the SPSS program. The total population of 567 employees with executive positions. The study was conducted at BUMN in West Java. Researchers set a sample size of 60 people with random techniques. Conclusions from the results of this study, namely (1) employee tenure has a fairly strong relationship with human resource quality; (2) employee tenure has a strong enough relationship with organizational commitment; and (3) human resource quality has a strong enough relationship with organizational commitment.